STRATEGI KAMPANYE PERSATUAN RADIO SIARAN SWASTA NASIONAL INDONESIA (PRSSNI) DALAM MEMPERKUAT POSITIONING RADIO (Studi Kasus Pada Kampanye PRSSNI bertajuk “Siaran Terakhir”) - Ita Suryani; Mochammad Zehhan; Sandra Olifia; Denny Erica (Jurusan Ilmu Komunikasi UTM, 2019)
In today’s digital era, public attention has shifted into digital media in their activities. Digital era has made most of the industries being disrupted, without exception the mass media industries, not only print, but also radio and television. Many advertisers or brands look at digital channels to campaign and leave conventional channels such as radio and print media as the media. Based on these conditions, radio needs to make a positioning strategy. The importance of positioning strategies brings developments for radio stations that are trying to increase their positions in the market with their listeners. The Indonesian National Private Broadcast Radio Association (PRSSNI) which accommodates all private radios in Indonesia, especially DKI Jakarta, organizes a Public Relations campaign titled